Gamification via mobile applications: A longitudinal examination of its impact on attitudinal loyalty and behavior toward a core service. Issue 6 (26th February 2021) - Kunkel, Thilo; Lock, Daniel; Doyle, Jason P.
Abstract: Organizations increasingly use gamification to engage with, and influence, consumers' attitudes and behaviors. In this article, we present findings from a longitudinal, mixed‐method research design that (1) examined the extent to which game design elements created by a third‐party app lead to increased attitudinal loyalty toward core service providers and (2) sought to explain the underlying processes that invoke attitudinal change. Behavioral data collected from app users indicated that knowledge‐focused affordances positively influenced consumer loyalty and explained 11.3% of the variance in attitudinal change. Follow‐up interviews revealed that Rewards, Competition, Sense of Achievement, and Gaining Knowledge were representative of consumers' motives for using the app, and Engagement and Identity explained how using the gamified application influenced users' attitudinal loyalty toward the core service. Overall, we contribute to knowledge about how gamified affordances can be used to add value to consumer experiences, both in relation to the gamified consumption experiences, and the focal brand that is serviced by a third‐party app.